The Redefining Scientific Literacy through AI-Augmented Contextual Learning: Preparing Future-Ready Students in a Digital Era: Redefining Scientific Literacy Through AI-Augmented Contextual Learning for Future-Ready Student - Nadia Putri; Stefanie Astrid Aipassa (Postgraduate Program, University of Mataram, 2025)
The rapid evolution of Artificial Intelligence (AI) has fundamentally transformed the educational landscape, reshaping how students learn, interact, and construct scientific understanding. This study seeks to redefine the construct of scientific literacy through the integration of AI-augmented contextual learning, aiming to prepare future-ready students capable of thriving in an era characterized by digital complexity and global interconnectivity. Using a mixed-methods design, this research examines the impact of AI-assisted contextual learning—utilizing intelligent tutoring systems, adaptive simulations, and data-driven feedback mechanisms—on students’ conceptual understanding, critical reasoning, and inquiry-based engagement in science learning. Quantitative findings indicate that students exposed to AI-augmented environments demonstrate significantly higher retention and application of scientific concepts compared to those taught through conventional methods. Qualitative analyses further reveal that AI tools foster metacognitive awareness, curiosity-driven exploration, and ethical sensitivity in scientific inquiry. The study emphasizing adaptability, creativity, and human–machine collaboration as integral dimensions of modern scientific understanding.